(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2025)
This paper analyzes the evolution of case law on the validity of electronic signatures in fintech contracts in Argentina since the enactment of two legal provisions recognizing them, Law 25,506 and subsequently Article 288 of the Civil and Commercial Code of the Nation, with authors disagreeing on their effectiveness. The significant impact of the use of technological tools in legal relationships, particularly in contracts with electronic signatures in fintech contracts, meant that case law initially did not recognize their effectiveness, especially in enforcement proceedings for the collection of money loans. Through the analysis of court cases, it is shown how case law has evolved in its interpretation and application of electronic signatures, highlighting the importance of security and authentication in digital transactions. Finally, it is concluded that electronically signed documents are subject to enforcement proceedings and should be legally recognized as valid instruments for the preparation of enforcement proceedings.